Biomarkers in migraine: a sea of something - Joshi, Siddharth; Iqbal, Roshan; Harsha, S.; Nemichandra, S. C.; Paneyala, Shasthara (International Journal of Research in Medical Sciences, 2020)
Migraine is the most common headache disorder with high prevalence. Clinical features which forms basis for diagnosis are heterogenous, varying from person to person and in an individual patient from one headache to the next. In most of the migraineurs treatment is delayed, until the disease severity is high leading to significant disability and socioeconomic burden. Many patients receive various combination of prolonged therapy with no significant benefits. Identifying a biomarker for migraine might help in assessing the susceptibility, diagnosing the disease early, choosing appropriate therapeutic target and monitoring the disease course. Here in this review authors discuss most studied, promising biomarkers emerging in field of migraine. The keywords migraine, and biomarkers were used in the search engines of PubMed and Google scholar and articles identified were extensively reviewed. Genetic biomarkers ascertain susceptibility or predisposition to migraine and are valuable in diagnosis, developing novel therapeutic agents, assessing treatment response. This review briefs about most studied genetic and circulatory biomarkers of migraine. Further research into existing biomarkers with higher sample size, excluding confounding factors is necessary. Search for newer biomarkers which can be of great value in diagnosis and therapy is needed. Identifying a biomarker which is reliable, replicable, easily available and cost-effective is need of the hour in management of migraine.